2015
DOI: 10.1021/acs.joc.5b01871
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and Enantioselective Addition and β-Hydrogen Transfer Reduction of Carbonyl Compounds with Diethylzinc Reagent in One Pot Catalyzed by a Single Chiral Organometallic Catalyst

Abstract: Using a single chiral phosphoramide-Zn(II) complex as the catalyst, the asymmetric β-H transfer reduction of aromatic α-trifluoromethyl ketones and enantioselective addition of aromatic aldehydes with Et2Zn in one pot were successfully realized, affording the corresponding additive products of secondary alcohols in high yields (up to 99%) with excellent enantioselectivities (up to 98% ee) and the reduction products of α-trifluoromethyl alcohols in good to excellent yields with up to 77% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…dAbsolute configuration was assigned by comparison with the product known from the literature. 13,14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…dAbsolute configuration was assigned by comparison with the product known from the literature. 13,14 …”
Section: Resultsmentioning
confidence: 99%
“… a Reaction conditions: BINOL/[Ti]/aldehyde/Et 2 Zn (0.1/1.4/1.0/3.0). b Reaction time: 30 min. Yield determined by GC in the presence of dodecane as the internal reference. c Measured by GC using a CP-Chirasil-Dex chiral column. d Absolute configuration was assigned by comparison with the product known from the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…Earlier in 2015, Song et al described enantioselective zinccatalyzed domino transfer reduction/ethylation reaction of aryl a-trifluoromethylketones 337, 338 with ZnEt 2 performed in the presence of 30 mol% of chiral 1,2-amino phosphoramide ligand 339 [149]. The process included the asymmetric b-H transfer reduction of the aryl a-trifluoro ketones and the enantioselective addition of ZnEt 2 to the aromatic aldehyde moieties (Scheme 114).…”
Section: Other Domino Reactionsmentioning
confidence: 99%
“…In 2015, Song et al demonstrated that chiral 1,2-amino phosphoramide ligand 110 was efficient in both the asymmetric β-H transfer reduction of aryl α-trifluoromethylketones 111,112 and enantioselective addition of ZnEt 2 of aromatic aldehydes performed in one-pot under the same reaction conditions [67]. As shown in Scheme 30, the corresponding chiral fluorinated diols 113,114 were obtained from the domino transfer reduction/ethylation reaction performed in toluene at -20 °C in the presence of 30 mol% of ligand 110 in high yields (86-90%) with excellent enantioselectivities (92-97% ee) albeit combined with moderate diastereoselectivities (40-42% de).…”
Section: Reactions Using 12-diamine Ligandsmentioning
confidence: 99%